Immune cells and their related genes provide a new perspective on the common pathogenesis of ankylosing spondylitis and inflammatory bowel diseases - Yimei Ding; Yue Yang; Luan Xue (Frontiers in Immunology, 2023)
BackgroundThe close relationship between ankylosing spondylitis (AS) and inflammatory bowel diseases (IBD) has been supported by many aspects, including but not limited to clinical manifestations, epidemiology and pathogenesis. Some evidence suggests that immune cells actively participated in the pathogenesis of both diseases. However, information on which cells are primarily involved in this process and how these cells mobilize, migrate and interact is still limited.MethodsDatasets were downloaded from Gene Expression Omnibus (GEO) database. Common differentially expressed genes (coDEGs) were identified by package “limma”. The protein-protein interaction (PPI) network and Weighted Gene Co-Expression Network Analysis (WGCNA) were used to analyze the interactions between coDEGs. KEGG pathway enrichment analysis and inverse cumulative distribution function were applied to identify common differential pathways, while Gene Set Enrichment Analysis (GSEA) was used to confirm the significance. Correlation analysis between coDEGs and immune cells led to the identification of critical immune-cell-related coDEGs. The diagnostic models were established based on least absolute shrinkage and selection operator (LASSO) regression, while receiver operating characteristic (ROC) analysis was used to identify the ability of the model. Validation datasets were imported to demonstrate the significant association of coDEGs with specific immune cells and the capabilities of the diagnostic model.ResultsIn total, 67 genes were up-regulated and 185 genes were down-regulated in both diseases. Four down-regulated pathways and four up-regulated pathways were considered important. Up-regulated coDEGs were firmly associated with neutrophils, while down-regulated genes were significantly associated with CD8+ T−cells and CD4+ T−cells in both AS and IBD datasets. Five up-regulated and six down-regulated key immue-cell-related coDEGs were identified. Diagnostic models based on key immue-cell-related coDEGs were established and tested. Validation datasets confirmed the significance of the correlation between coDEGs and specific immune cells.ConclusionThis study provides fresh insights into the co-pathogenesis of AS and IBD. It is proposed that neutrophils and T cells may be actively involved in this process, however, in opposite ways. The immue-cell-related coDEGs, revealed in this study, may be relevant to their regulation, although relevant research is still lacking.